Sociodemographic determinants of willingness to adopt surveillance technology and mosquito control training for dengue in Malaysia - Mahfodz, Zulfadli; Dapari, Rahmat; Salleh, Siti Aekbal; Camalxaman, Siti Nazrina; Aljaafre, Ahmad Falah; Che Dom, Nazri (Nature Research, 2026)
Dengue fever remains a major public health concern in Malaysia, where rapid urbanization and ineffective vector control measures contribute to persistent outbreaks. While drone-based mosquito surveillance and mobile applications offer innovative solutions, public acceptance and adoption remain uncertain. Additionally, community-based mosquito control training is crucial, yet participation is often influenced by sociodemographic factors. This study examines determinants influencing willingness to adopt a dengue surveillance mobile application and engage in mosquito control training programs. A cross-sectional survey was conducted across multiple states in Peninsular Malaysia, using a stratified random sampling approach. Data were collected via online and face-to-face surveys from 866 respondents (≥ 18 years, residing for at least 6 months). The questionnaire assessed sociodemographic characteristics, perceptions of drone-based surveillance and willingness to download a dengue surveillance application. Multinomial logistic regression was used to identify significant predictors of engagement. Younger respondents (18–30 years) were more likely to download the dengue surveillance app, while older individuals (> 40 years) were more interested in training programs (p < 0.05). Longer residence (> 3 years) increased willingness to adopt digital mosquito surveillance. Males were 1.9 times more likely to participate in training, while housing type influenced engagement, with terrace house residents being 1.7 times more likely to join. Negative perceptions of drone surveillance significantly reduced app adoption (p = 0.001), but training participation was unaffected. This study highlights sociodemographic disparities in dengue vector control engagement. Younger populations prefer technology-driven interventions, while older individuals favor community-based training. Addressing drone concerns, enhancing digital literacy, and integrating technology with traditional approaches is key to optimizing dengue control efforts.